Pozycja strefy euro w gospodarce światowej - Mucha-Leszko, Bogumiła (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The aim of this article is to evaluate the Euro Area as one of the main centres of the World Economy on the basis of 3 criteria which, in the author's view, provide the best demonstration of the results to date of functioning of the Economic and Monetary Union, as well as possibilities to increase the role of the Euro Area in the future. The criteria are as follows: 1) economic growth, 2) growth of labour productivity, 3) innovative position. The analysis is of comparative character using the US economic performance as a point of reference. Based on this analysis the following conclusions have been made: 1. Significantly lower growth dynamics in the Euro Area compared to the USA between 1999 and 2006. GDP growth was higher in the Euro Area only in 2001. 2. Lower labour productivity in the Euro Area. Since the mid-1990's, the rate of labour productivity growth has been increasing in the US and decreasing in the Euro Area. This unfavourable tendency deepened between 2000 and 2005. 3. Lower innovativeness of the Euro Area compared to the US and Japan, however a considerable internal diversity can be observed in the Euro Area in this regard. Member states can be divided into 4 categories: leaders of innovation, following the leaders, catching up and lagging behind. 4. Increase in the Euro Area technology gap towards the US and Japan can be explained by lower ICT expenditures. 5. The technology gap between the Euro Area and the US is narrowing faster (it is stable tendency since 2003). Significant decrease in the gap towards Japan did not occured until the year 2006. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 348-362